Effect of N alpha-methyl-histamine on acid secretion in isolated cultured rabbit parietal cells: implications for Helicobacter pylori associated gastritis and gastric physiology. Issue 1 (January 1997) - Beales, I L; Calam, J
Abstract : BACKGROUND: Helicobacter pylori has been shown to produce the unusual metabolite N alpha-methyl-histamine. This compound is known to be a potent agonist at inhibitory histamine H3 receptors. There is increasing evidence implicating this receptor in the control of gastric acid secretion but the mechanism for this remains to be clarified. AIMS: To investigate the effect of N alpha-methyl-histamine on the acid secretory activity of parietal cells and to determine the mechanism for such effects, thus helping to determine the role of this compound in the pathophysiology of H pylori infection. METHODS: Rabbit parietal cells were isolated and enriched by collagenase-EDTA digestion and centrifugal elutriation. Following culture on Matrigel coated plates, acid secretion was assessed by 14C aminopyrine accumulation. RESULTS: N alpha-methyl-histamine (100 microM) was as potent as histamine (100 microM) in stimulating acid secretion. This effect was reversed by ranitidine indicating it was mediated via the H2 receptor. N alpha-methyl-histamine potentiated the effects of both carbachol (increased by 280%) and gastrin (by 350%) (p < 0.01). N alpha-methyl-histamine had no inhibitory actions on forskolin or carbachol stimulated acid secretion suggesting that there is not an inhibitory H3 receptor located directly on the parietal cell. CONCLUSIONS: Bacterially produced N alpha-methyl-histamine directly stimulates acid secretion by parietal cells and this may contribute to the increased acid secretion that contributes to duodenal ulceration.